Developing and applying optoelectronics in machine vision - Sergiyenko, Oleg 1969-; Rodríguez-Quiñonez, Julio C. 1985- (Advances in computational intelligence and robotics (ACIR) book series, 2017)
This book evaluates emergent research and theoretical concepts in scanning devices and 3D reconstruction technologies being used to measure their environment, examining the development of utilization of machine vision practices and research, optoelectronic devices, and sensor technologies